Rola państwa w procesie tworzenia i rozwoju struktur klastrowych w Polsce - Pilarska, Czesława (The Role of Government in the Process of Creation and Development of Clusters in Poland, 2009)
The paper describes government activities in the process of creation of clusters structures in Poland. The article consists of three parts. The first part presents a definition of clusters, the second one describes initiatives of clusters in Poland. The third part shows the role of government in the process of cluster creation. In the article, it was emphasized that there is no specific cluster based policy in Poland, but it is a part of the innovation policy. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 799-815